Multivariate statistical methods - Morrison, Donald F. (Thomson/Brooks/Cole, 2005)
Contents: Chapter 1: Samples from the multivariate normal population; Chapter 2: Tests of hypotheses on means; Chapter 3: The multivariate analysis of variance; ...